Multiple endocrine neoplasia phenocopy revealed as a co‐occurring neuroendocrine tumor and familial hypocalciuric hypercalcemia type 3. Issue 10 (18th August 2016) - Hovden, Silje; Jespersen, Marie Louise; Nissen, Peter H.; Poulsen, Per Løgstrup; Rolighed, Lars; Ladefoged, Søren A.; Rejnmark, Lars
Key Clinical Message: Familial hypocalciuric hypercalcemia type 3 should be considered as differential diagnosis in patients with suspected primary hyperparathyroidism and/or suspected multiple neoplasia syndrome, as correct diagnosis will spare the patients for going through multiple futile parathyroidectomies and for the worry of being diagnosed with a cancer susceptibility syndrome. Abstract : Familial hypocalciuric hypercalcemia type 3 should be considered as differential diagnosis in patients with suspected primary hyperparathyroidism and/or suspected multiple neoplasia syndrome, as correct diagnosis will spare the patients for going through multiple futile parathyroidectomies and for the worry of being diagnosed with a cancer susceptibility syndrome.